2014
DOI: 10.1016/j.bbrc.2014.08.131
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine inhibits the proliferation and survival of B-cell acute lymphoblastic leukemia cell lines irrespective of glucocorticoid resistance

Abstract: Piperlongumine (PL), a pepper plant alkaloid from Piper longum, has anti-inflammatory and anti-cancer properties. PL selectively kills both solid and hematologic cancer cells, but not normal counterparts. Here we evaluated the effect of PL on the proliferation and survival of B-cell acute lymphoblastic leukemia (B-ALL), including glucocorticoid (GC)-resistant B-ALL. Regardless of GC-resistance, PL inhibited the proliferation of all B-ALL cell lines, but not normal B cells, in a dose- and time-dependent manner … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Furthermore, the immunoproteasome is slightly more efficient than the 20S proteasome in recognizing and degrading nascent oxidant-damaged proteins [33]. Recent studies have demonstrated that piperlongumine contributes to cancer cell death by targeting stress responses to ROS [9, 3436]. Consistent with these studies, we found that piperlongumine increased intracellular ROS levels in MM cells.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the immunoproteasome is slightly more efficient than the 20S proteasome in recognizing and degrading nascent oxidant-damaged proteins [33]. Recent studies have demonstrated that piperlongumine contributes to cancer cell death by targeting stress responses to ROS [9, 3436]. Consistent with these studies, we found that piperlongumine increased intracellular ROS levels in MM cells.…”
Section: Discussionsupporting
confidence: 89%
“…Piperlongumine is an alkaloid isolated from the long pepper ( Piper longum L. ) that possesses anti-inflammatory, anti-platelet aggregation, and anti-tumor properties [79]. Piperlongumine exerts anti-tumor effects through a variety of pathways, including the induction of reactive oxygen species (ROS) accumulation, activation of C/EBP homologous protein (CHOP), suppression of LMP-1 (EBV-encoded oncogene) expression, activation of AMPK phosphorylation, inhibition of NF-κB, and promotion of autophagy [1017].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the GC resistance‐promoting role of MYC in ALL was firstly elucidated by Renner K . Han et al revealed that MYC displays constitutive activation in B‐ALL cell lines, especially GC‐resistant B‐ALL, indicating the critical role of MYC in evolution of GC resistance . The positive impact of MYC on progression of GC resistance in ALL was subsequently strengthened by other studies .…”
Section: Discussionmentioning
confidence: 96%
“…Despite the reassuring achievements in the treatment of patients with ALL, resistance to GC agonists has been a major obstacle in eliminating leukemia cells and maximizing cure . Several studies on GC resistance have elucidated that GC‐stimulated apoptosis is not induced in leukemia cells with poor response to GC agents . Recently published articles partly expanded our understanding about the molecular mechanism of GC resistance, wherein the role of some molecules and signaling pathways including MLL rearrangement and JAK/SAT pathway alteration were determined.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the helix-loop-helix/ leucine-zipper transcription factor family, MYC is a master regulator of important biological processes such as cell survival, proliferation, differentiation, metabolism and pluripotency maintenance (58,59). Constitutive activation of MYC exhibited in a variety of B-ALL cell lines (60). Double transgenesis of MYC and Bcl-2 caused hyperproliferation of pre-B and B cells and promoted initiation of B-ALL in mice (51).…”
Section: Discussionmentioning
confidence: 99%